Achieving high-resolution spatial mapping of dose and linear energy transfer in ion-beam therapy - Jensen, Mads Lykke; Togno, Michele; Muñoz, Iván Domingo; Brons, Stephan; Jäkel, Oliver; Yukihara, Eduardo G; Christensen, Jeppe Brage (Physics in medicine and biology, 2025)
Objective. We present a novel detector system capable of simultaneously obtaining two-dimensional (2D) dose and linear energy transfer (LET) maps from Al2O3 films of sizes up to mm2 using optically stimulated luminescence (OSL). Approach. The system is based on the OSL from doped Al2O3 films measured using pulsed stimulation and time-resolved OSL detection. The system was calibrated in 1H-, 4He-, and 12C-ion beams. The minimal detectable dose (MDD), response homogeneity, pixel cross-stimulation, and precision were also investigated. To demonstrate the system’s performance, 2D maps of dose and LET of a proton Bragg curve were measured. Main results. The system was demonstrated to be capable of obtaining absorbed dose and LET 2D maps with a spatial resolution set to mm2. The system was calibrated over a clinically relevant range of LET values and characterized through assessment of MDD (25 mGy), readout protocols, response homogeneity, precision, and relative detector efficiency. Dose and LET were found to be measurable with precisions of 3.2% and 10%, respectively. Significance. To our knowledge, this is the first passive detector system capable of measuring LET and dose simultaneously in 2D with a 1.0 mm2 spatial resolution requiring no prior information. Such properties are required to experimentally validate simulated dose and LET distributions in ion-beam therapy, paving the way for sub-mm mapping of radiation-induced relative biological effectiveness.
Veröffentlicht: 24. Oktober 2025
Gesehen am 04.12.2025